A Randomized, Single-Blind, Group Sequential, Active-Controlled Study to Evaluate the Clinical Efficacy and Safety of α-Lipoic Acid for Critically Ill Patients With Coronavirus Disease 2019 (COVID-19) - Zhong, Ming; Sun, Aijun; Xiao, Ting; Yao, Ge; Sang, Ling; Zheng, Xia; Zhang, Jinyan; Jin, Xuejuan; Xu, Lei; Yang, Wenlong; Wang, Peng; Hu, Kai; et al. (Frontiers in Medicine, 2022)
Aim: To evaluate the clinical efficacy and safety of α-Lipoic acid (α-LA) for critically ill patients with coronavirus disease 2019 (COVID-19). Methods: This study was an investigator-initiated, single-center, single-blinded, feasibility, randomized clinical trial conducted at the JinYinTan Hospital, Wuhan, China between February 2020 and March 2020. 17 patients, who were admitted with critically ill COVID-19, were randomly assigned in a 1:1 ratio to receive either α-LA group or placebo group. Statistical analysis was performed in April 2020. For patients randomized to placebo group, standard care plus equal volume saline infusion (placebo) would be given for 7 days after enrollment. In the α-LA group, patients would receive α-LA (1200 mg/d, intravenous infusion) once daily plus standard care for 7 days. All patients were monitored within the 7 days therapy and followed up to day 30 after therapy. The primary outcome was the Sequential Organ Failure Estimate (SOFA) score. Secondary outcome was the all-cause mortality within 30 days. Results: In total, 17 patients (median age, 63 years [interquartile range, 59-66 years]; 13 men [76.47%]) were included, of whom 8 were randomized to the α-LA group and 9 to the placebo group. SOFA score was similar at baseline, increased from 4.3 to 6.0 in the placebo group and increased from 3.8 to 4.0 in the α-LA group (P=0.36) after 7 days. The 30-day all-cause mortality tended to be lower in the α-LA group (37.5%) compared to that in the placebo group (77.8%, P=0.09). Conclusions: In our study, α-LA use is associated with lower SOFA score increase and lower 30-day all-cause mortality as compared with the placebo group. Although the mortality rate was two-folds higher in placebo group than in α-LA group, only borderline statistical difference was evidenced due to the limited patient number. Future studies with larger patient cohort are warranted to validate the role of α-LA in critically ill patients with COVID-19.